2003
DOI: 10.1108/09649420310491486
|View full text |Cite
|
Sign up to set email alerts
|

The career development and aspirations of women in middle management – revisited

Abstract: This article reports the results of the second phase of a research study on the career development and aspirations of women in middle management in business firms in the USA. The major method of this research study was the individual case study. Case studies relied on in-person and/or telephone interviews with the same 30 women managers who participated in the first phase of the study in 1995. The majority of the women managers worked for Fortune 500 companies and were located throughout the USA. The findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
63
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 13 publications
3
63
2
3
Order By: Relevance
“…That educational level has significant influence on women's career development is similar to that reported by Wentling (2003). He found that development of women to top managerial positions depends on their education.…”
supporting
confidence: 78%
“…That educational level has significant influence on women's career development is similar to that reported by Wentling (2003). He found that development of women to top managerial positions depends on their education.…”
supporting
confidence: 78%
“…Studies on personal factors in career development emphasize gender and gender role socialization (Astin, 1984;Betz & Fitzgerald, 1987;Eag1y, 1987;Gottfredson, 1996); personality (Betz & Fitzgerald;Ritchie, Fassinger, Linn, Johnson, Prosser, & Robinson, 1997;Wentling, 2003;White, 1995); the acquisition and development of human capital such as education, formal skills/abilities, and job tenure (Burke, 2007;Knoppers, 1992); and self-efficacy (Betz, 2004;Lent et aI., 1994). Eccles (1994) posited, "Understanding women's occupational choices requires a broad view of the options and roles available to women" (p. 605).…”
Section: Personal Factors Personal Factors Include a Range Of "Intramentioning
confidence: 99%
“…Understanding the personality characteristics of women in executive management positions has been widely studied (Richie et aI., 1997;Wentling, 1996Wentling, ,2003White, 1995). Women in leadership positions have been described as committed, dedicated, passionate, and self-confident.…”
Section: Personal Factors Personal Factors Include a Range Of "Intramentioning
confidence: 99%
See 2 more Smart Citations